The Model of Motivation, Organizational Commitment, Organizational Culture, and Leadership on Turnover through Job Satisfaction - Rohana Sitanggang; Aswanti Setyawati; Sugiyanto Sugiyanto; Rr. Endang Wahyuni; Olfebri Olfebri; Primadi Candra Susanto (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to identify the factors that affect employee turnover through job satisfaction in airports in Indonesia. This research employs a literature review approach by synthesizing findings from various previous international, indexed scientific publications related to the research topic. The study uses a descriptive qualitative method with a literature review design. Data were obtained from reputable international indexed journals sourced from databases such as Scopus, Web of Science, Emerald, Springer, and Google Scholar. The selected literature was examined using data reduction techniques, matrix-based data presentation, and comparative synthesis to identify patterns, similarities, and differences among the studies. The findings indicate that motivation, organizational commitment, organizational culture, and leadership have an influence on employee turnover in Indonesian airports, both directly and indirectly through job satisfaction. However, this study has several limitations. Since it relies on a literature review approach, the results remain conceptual and depend heavily on the quality and scope of previous studies, without incorporating primary empirical data from airport employees. Furthermore, the generalizability of the findings is limited to the context of Indonesian airports and sectors with similar operational characteristics. This study provides a conceptual contribution by integrating the effects of motivation, organizational commitment, organizational culture, and leadership on employee turnover through job satisfaction within the airport context. The novelty of this research lies in the integration of four key human resource management factors into a single conceptual framework, highlighting the role of job satisfaction as a mediating mechanism in explaining employee turnover in the airport sector, which has not been extensively explored in previous studies.